(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
Hikayat Hang Tuah (HHT) is a masterpiece rich with elements of Malay culture. In the HHT, loyalty is a significant value and a cornerstone of Malay culture. Therefore, in the context of translation, the effectiveness of conveying this value is crucial for cross-cultural interaction between the source language culture and target language culture. To evaluate this effectiveness, this study examines the culture value of loyalty in HHT through the perspective of cultural translation, employing the Discourse and Register Analysis Theory. Analysis of discourse containing the culture of loyalty reflected through the character of Hang Tuah from the Malay source text (Hikayat Hang Tuah) to the Chinese target text (Hang Du A Chuan Qi) is conducted through three main aspects of register: field of discourse, mode of discourse, and tenor of discourse. The findings indicate that the translator tends to maintain important elements in the field of language and tenor of language. Particularly, in the aspect of language mode, the translator translates court language to the target text using terms from China’s feudal era to maintain the hierarchy and decorum characteristic of Malay court culture. Additionally, the translator’s use of religious terms in forms appropriate to the context of target language also clarifies Hang Tuah’s loyalty to the king and religion for target language readers. These efforts not only ensure the preservation of Malay cultural values of loyalty but also foster understanding of cross-cultural interaction between the Malay and Chinese societies. Full text: PDF